2020
DOI: 10.1007/s11356-020-10522-8
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic effect of γ-Al(OH)3, α-FeOOH, and α-Fe2O3 on the ozonation-based decomposition of diethyl phthalate adsorbed on sand and soil

Abstract: Diethyl phthalate (DEP) is a pollutant which can be found on soils as a result of its widespread application in plastic industry. Soil contaminated with DEP requires the application of different chemical methods to attain its remediation. Among these methods, ozonation has proven to be effective against toxic soil pollutants. The presence of metal oxides in soil is a possible source of catalytic effect. In this study, it was analyzed the catalytic effect of goethite (α-FeOOH), hematite (α-Fe 2 O 3 ), and gibbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Heterogeneous catalytic ozonation is a promising technology for the degradation and mineralization of refractory pollutants in an aqueous solution . The catalysts used for this purpose mainly include (1) metal oxides (e.g., MnO 2 , , Al 2 O 3 , , CeO 2 , , and FeOOH , ); (2) silicate materials (e.g., zeolite, , MCM-41, SBA-15, and cordierite); (3) metal and metal oxides-supported catalysts (e.g., Cu/Al 2 O 3 , MnO X /Al 2 O 3 , Co/AC, and FeOOH/Al 2 O 3 ); and (4) activated carbon (AC). , Among these catalysts, γ-Al 2 O 3 -supported metal oxides show high activity for the catalytic oxidation of aromatic compounds and MnO 2 has an outstanding performance among the first transition metal. , The catalytic activity of MnO 2 is positively correlated with the number of surface hydroxyl groups and oxygen vacancies, and it can be improved by combining other metals such as Cu, Fe, and Ce oxides. , Li et al found that Cu/Mn-loaded γ-Al 2 O 3 showed enhanced catalytic activity for the removal of Acid Red B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous catalytic ozonation is a promising technology for the degradation and mineralization of refractory pollutants in an aqueous solution . The catalysts used for this purpose mainly include (1) metal oxides (e.g., MnO 2 , , Al 2 O 3 , , CeO 2 , , and FeOOH , ); (2) silicate materials (e.g., zeolite, , MCM-41, SBA-15, and cordierite); (3) metal and metal oxides-supported catalysts (e.g., Cu/Al 2 O 3 , MnO X /Al 2 O 3 , Co/AC, and FeOOH/Al 2 O 3 ); and (4) activated carbon (AC). , Among these catalysts, γ-Al 2 O 3 -supported metal oxides show high activity for the catalytic oxidation of aromatic compounds and MnO 2 has an outstanding performance among the first transition metal. , The catalytic activity of MnO 2 is positively correlated with the number of surface hydroxyl groups and oxygen vacancies, and it can be improved by combining other metals such as Cu, Fe, and Ce oxides. , Li et al found that Cu/Mn-loaded γ-Al 2 O 3 showed enhanced catalytic activity for the removal of Acid Red B.…”
Section: Introductionmentioning
confidence: 99%
“…4 Heterogeneous catalytic ozonation is a promising technology for the degradation and mineralization of refractory pollutants in an aqueous solution. 5 The catalysts used for this purpose mainly include (1) metal oxides (e.g., MnO 2 , 6,7 Al 2 O 3 , 8,9 CeO 2 , 10,11 and FeOOH 12,13 ); (2) silicate materials (e.g., zeolite, 14,15 MCM-41, 16 SBA-15, 17 and cordierite 18 ); (3) metal and metal oxides-supported catalysts (e.g., Cu/Al 2 O 3 , MnO X /Al 2 O 3 , Co/AC, and FeOOH/Al 2 O 3 ); 19−22 and (4) activated carbon (AC). 23,24 Among these catalysts, γ-Al 2 O 3supported metal oxides show high activity for the catalytic oxidation of aromatic compounds and MnO 2 has an outstanding performance among the first transition metal.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, adsorptive removal proves to be effective for PAEs remediation, but presents high costs and requires further treatment. Finally, advanced oxidation processes (AOPs) have been considered as pertinent methodologies to remove phthalates from wastewaters [20,21], including the photochemically enhanced Fenton reaction [22,23], the combinations of TiO 2 or H 2 O 2 with ultraviolet (UV) light irradiation [20,24], ozonation reactions [25,26], and catalytic ozonation processes [27][28][29].…”
Section: Introductionmentioning
confidence: 99%